Look who’s TORking: mTOR-mediated integration of cell status and external signals during limb development and endochondral bone growth - H’ng, Chee Ho; Khaladkar, Ashwini; Rosello-Diez, Alberto (Frontiers in Cell and Developmental Biology, 2023)
The balance of cell proliferation and size is key for the control of organ development and repair. Moreover, this balance has to be coordinated within tissues and between tissues to achieve robustness in the organ's pattern and size. The tetrapod limb has been used to study these topics during development and repair, and several conserved pathways have emerged. Among them, mechanistic target of rapamycin (mTOR) signaling, despite being active in several cell types and developmental stages, is one of the least understood ones in limb development, perhaps because of its multiple potential roles and interactions with other pathways. In the body of this review, we have collated and integrated what is known about the role of mTOR signaling in three aspects of tetrapod limb development: 1) limb outgrowth; 2) chondrocyte differentiation after mesenchymal condensation and 3) endochondral ossification-driven longitudinal bone growth. We conclude that, given its ability to interact with the most common signaling pathways, its presence in multiple cell types, and its ability to influence cell proliferation, size and differentiation, the mTOR pathway is a critical integrator of external stimuli and internal status, coordinating developmental transitions as complex as those taking place during limb development. This suggests that the study of the signaling pathways and transcription factors involved in limb patterning, morphogenesis and growth could benefit from probing the interaction of these pathways with mTOR components.